Decoding Hydrogen-Bond Network of Electrolyte for Cryogenic Durable Aqueous Zinc-Ion Batteries - Wei, Xiyan; Guan, Jinpeng; Mu, Yongbiao; Zou, Yuhan; Wei, Xianbin; Yang, Lin; Man, Quanyan; Yang, Chao; Zang, Limin; Sun, Jingyu; Zeng, Lin (Nano-Micro Letters, 2026)
Aqueous zinc-ion batteries (AZIBs) hold great promise for next-generation energy storage but face challenges such as Zn dendrite growth, side reactions, and limited performance at low temperatures. Here, we propose an electrolyte design strategy that reconstructs the hydrogen-bond network through the synergistic effect of glycerol (GL) and methylsulfonamide (MSA), enabling the formation of a (100)-oriented Zn anode. This design significantly broadens the operating current and temperature windows of AZIBs. As a result, Zn||Zn symmetric cells exhibit remarkable cycling stability, achieving 4,000 h at 1 mA cm−2 and 600 h at 40 mA cm−2 (both at 1 mAh cm−2 capacity); even at −20 °C, Zn||Zn symmetric cells deliver ultra-stable cycling for over 5,400 h. Furthermore, Zn||VO2 full cells retain 77.3% of their capacity after 2,000 cycles at 30 °C with a current density of 0.5 A g−1 and 85.4% capacity retention after 2,000 cycles at −20 °C and 0.25 A g−1. These results demonstrate a robust pathway for enhancing the practicality and low-temperature adaptability of AZIBs. Highlights: 1 The hydrogen-bond network structure and solvation structure of the electrolyte are reconstructed by glycerol (GL) and methylsulfonamide (MSA) to achieve low-temperature durability in aqueous zinc-ion batteries (AZIBs). 2 GL and MSA collaboratively construct (100)-oriented high-activity dendrite-free zinc anode to improve the rate performance of AZIBs. 3 The Zn||Zn symmetrical cell achieved stable operation for 4,000 h at 1 mA cm−2 and 1 mAh cm−2 (30 °C) and 5,400 h at 0.5 mA cm−2 and 0.5 mAh cm−2 (−20 °C).